Endovascular Treatment versus Best Medical Treatment in Patients with Acute Ischemic Stroke: A Meta-Analysis of Randomized Controlled Trials - Qureshi, A.I.; Ishfaq, M.F.; Rahman, H.A.; Thomas, A.P. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Endovascular treatment has emerged as a minimally invasive technique for patients with acute ischemic stroke to achieve recanalization. Our aim was to determine the effects of endovascular treatment on clinical and safety outcomes compared with best medical treatment.MATERIALS AND METHODS: Fifteen randomized trials that compared endovascular treatment with best medical treatment in patients with acute ischemic stroke met the inclusion criteria. We calculated pooled odds ratios and 95% CIs by using random-effects models. The primary end point was a favorable outcome defined by a modified Rankin Scale score of 0 (no symptoms), 1 (no significant disability), or 2 (slight disability) at 90 days postrandomization.RESULTS: Of the 2980 subjects randomized, the proportion of subjects who achieved a favorable outcome was significantly greater among those randomized to endovascular treatment compared with best medical treatment (2949 subjects analyzed; odds ratio, 1.82; 95% CI, 1.38–2.40; P < .001). Excellent outcome (modified Rankin Scale score of 0 or 1) was also significantly greater among those randomized to endovascular treatment (2791 subjects analyzed; odds ratio, 1.77; 95% CI, 1.29–2.43, P < .001). Risk of symptomatic intracranial hemorrhage was similar between endovascular treatment and best medical treatment (2906 subjects analyzed; odds ratio, 1.19; 95% CI, 0.84–1.68; P = .34).CONCLUSIONS: Compared with best medical treatment, the odds of achieving a favorable outcome or excellent outcome at 3 months postrandomization are approximately 80% higher with endovascular treatment among patients with acute ischemic stroke.ICHintracranial hemorrhage